Social capital to develop religious moderation for Indonesia-Malaysia border communities - Kristianus, Kristianus; Prasetyo , Laurentius; Magdalena, Magdalena (The International Journal of Politics and Sociology Research, 2024)
This research is motivated by a religious moderation program that is being developed by the Ministry of Religion of the Republic of Indonesia. Apart from that, the border as this country's front porch with neighboring countries needs to be empowered by its people. Communities on the border, who are generally Dayak, need to explore their culture. Dayak people's understanding of religious moderation is also still limited. The aim of this research is to find a formula for social capital in developing religious moderation in border areas. The research method is descriptive qualitative with an ethnographic approach. The research team is the research subject, where the objects are traditional stakeholders and community leaders at the research location. Data collection techniques by interviewing research objects. Data analysis was carried out by codifying and grouping data based on answers to interviews conducted. The results of the grouping were then interpreted and then discussed again with the figures in the form of a Focus Group Discussion. In this way, the concept obtained is a joint conclusion of the parties involved in the research. The results of the research are that the social capital of border communities to develop religious moderation is very high. Social capital takes the form of good social interaction, customs and religious life. In border areas, although the conditions for providing education are still limited, they are inclusive. Academically, the results of this research can be used as a reference for developing a model of religious moderation.